USAGE OF GROUPWARE IN SOFTWARE ENGINEERING EDUCATION AT THE CSCW LABORATORY OF UNIVERSITY DUISBURG-ESSEN: POSSIBILITIES AND LIMITATIONS - Muhammad Iman Santoso (PSTE UNIMUS, 2008)
This paper analyzes the application level in CSCW laboratory there are Electronic meeting rooms, Video Conferencing, Desktop Conference (Passenger), and BSCW system which conducting in The University Duisburg – Essen Germany. This analysis included short analysis and discussion about possibilities and limitation of each experiment followed by outlook how this lab can be further developed.Multi-user to Multipoint Videoconferences is introduced to cover all of devices join to the conferences. A computer network, PSTN (Public Switched Telephone Network), ISDN Phone, Wireless Infrastructures (accessed by laptop, smart phone, PDA) and videoconferences systems is proposed to be integrated